Model Pemilihan Moda Transportasi antara Angkutan Umum Bus dan Shuttle Sebagai Upaya Peningkatan Pelayanan - Ratnasari, Sri Merita; Hendarto, Sri; Kusdian, Didin; Siregar, Chandra Afriade (Universitas Ibn Khaldun, 2024)
The existence of shuttle public transportation will result in a decrease in revenue from bus public transportation. Studying the level of influence of factors that influence the characteristics of the choice of transportation mode between bus public transportation and shuttle public transportation, especially in Sumedang Regency, reviewing simulations of changes in travel costs to determine the relationship between travel costs and levels. possibilities in choosing bus and shuttle public transportation. In this research, it can be concluded that the simplification of variables uses a simple correlation method and uses a stepwise method. Based on the calculation of the average level of probability of selecting shuttle and public bus modes, if shuttle and public buses serve the Sumedang - Jakarta route then the probability level of selecting shuttle mode is 51 % and public bus mode 49% with an average cost difference that is not too significant at Rp. 35,000 to Rp. 50,000,-. So in this research travel time and waiting time for departure are factors to consider in choosing public transport modes. On the Sumedang - Jakarta route or vice versa, the shuttle crosses the Cisumdawu Toll Road which connects Sumedang City - Cileunyi Bandung Toll Road and the MBZ Sheikh Mohammed Bin Zayed Flyover Toll Road which connects the Cikampek - Jakarta Toll Road, so the travel time on the Sumedang - Jakarta route is shorter using the shuttle. , while public buses are not allowed to cross the MBZ Elevated Toll Road. The study only analyzes the mode choice between bus and shuttle public transportation for the Sumedang – Jakarta route. The scope of this study can be expanded for passenger movements on other routes and competition for other modes.